Factors Affecting Lactation Length and Peak Milk Yield in Gir Cattle - Dangar, Nikhil S; Vataliya, Pravin H (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The production records of 228 Gir cows with 680 lactations sired by 52 bulls, maintained at Cattle Breeding Farm, Junagadh, were studied for 24 years (1987-2010). The data were analyzed to study the effect of period of calving, season of calving and parity as fixed effect on the production traits, viz., lactation length and peak milk yield. The least squares means of lactation length and peak milk yield in Gir cows were found to be 328.27 ± 12.99 days and 12.31 ± 0.51 kg, respectively. The variance analysis revealed that the period of calving and parity had a highly significant (p <0.01) influence on average lactation length and peak milk yield in Gir cows. Effect of season of calving was non- significant on these traits, indicating breed characteristic to adopt with tropical environment. There was precise decreasing trend in the lactation length due to parity or sequence of calving, indicating decrease of lactation length as the age advances, whereas peak milk yield increased gradually till 5th parity and then declined with advancing age/parity till 11th lactation. Lactation length ranged from 408.78 to 268.93 days in 1st to 12th parity, while peak milk yield in 1st, 5th and 10th lactation was 9.48, 13.65 11.17 kg, respectively.